Validation of the TadpoleTMCampylobacter jejuni Real-Time PCR Identification Kit. (23rd November 2019) - Jiang, Yuan; Shen, Jinling; Xue, Feng; Zhao, Lina; Yang, Jielin; Shao, Jingdong; Zhu, Changqing; Su, Jing; Chen, Yi; Brodsky, Michael; Salfinger, Yvonne
Abstract: Background: The gene-based real-time PCR method for identification of Campylobacter jejuni is more simple, rapid and accurate than the traditional biochemical method. Objective: A performance validation of the Tadpole TM Campylobacter jejuni Real-Time PCR Identification Kit was performed. Method: The assay uses TaqMan Real-time PCR technology to amplify target genes from isolated colonies. Bacterial deoxyribonucleic acid (DNA) from inclusivity and exclusivity organisms cultured on Columbia Blood Agar, Campy-Cefex agar and modified Charcoal Cefoperazone Deoxycholate was extracted and analyzed on three instruments: Applied Biosystems (ABI) 7500 Fast, ABI StepOne Plus and Bio-Rad CFX96. Results: When 57 distinct strains of C. jejuni were tested for inclusivity, all 57 strains produced positive results on the three instruments. In exclusivity testing, all 35 strains of related organisms, including 7 non-target Campylobacter strains and other common species, produced negative results on the three instruments. The Independent Laboratory validation consisting of an inclusivity and exclusivity evaluation for 10 C. jejuni isolates and 10 nontarget Campylobacter isolates also showed 100% expected results on the three instruments. In addition, in robustness testing, small, deliberate changes to the assay parameters, including cell suspension turbidity, heat lysis time, and DNA template volume in the PCR reaction, did not affect the kit performance. Finally, the combined lot-to-lot and stability study on both the ABI 7500 Fast and the ABI StepOne Plus showed that the 11 C. jejuni strains and 5 nontarget Campylobacter strains can be correctly identified by the three independently manufactured, lots and it supported a shelf life of 9 months when stored at –20°C. Conclusions: The Tadpole method offers a rapid, accurate, and robust alternative for C. jejuni identification. Highlights: Rapid and accurate method to identify C. jejuni, which has a good robustness and high stability. It is flexible and offers the advantages of reduced labor and time saving.